Clinical investigation of flat panel CT following middle ear reconstruction: a study of 107 patients - Plath, Karim; Kromeier, Jan; Neudert, Marcus; Beleites, Thomas; Zahnert, Thomas; Laszig, Roland; Offergeld, Christian (European radiology, 2014)
After middle ear reconstruction using partial or total ossicular replacement prostheses (PORP/TORP), an air-bone gap (ABG) may persist because of prosthesis displacement or malposition. So far, CT of the temporal bone has played the main role in the diagnosis of reasons for postoperative insufficient ABG improvement. Recent experimental and clinical studies have evaluated flat panel CT (fpCT) as an alternative imaging technique that provides images with high isovolumetric resolution, fewer metal-induced artefacts and lower irradiation doses.
Published online: 26 November 2013
Gesehen am 21.09.2020